Politične elite in tip kapitalizma - Adam, Frane (Teorija in praksa, 2008)
Despite their smallness, Slovenia and Estonia are economically and institutionally the most prominent post-communist countries, and since 2004 they are also members of European Union. However, they developed completely different - even diametrically opposite - institutional organisation and introduced different political and social arrangements. Besides the "path-dependence" reasons, one could set out as an important factor in these differences also the role of strategic decisions of political elite, its connections and ideological backgrounds. It is possible to claim that political elite in Estonia introduced a type of the state that is close to liberal-minimalist model, while Slovenia is closer to corporative model of social state. In both cases some dysfunctional effects appeared, which represent new challenge for elites and at the same time they are a test of their credibility and competence.
Keywords: Politične elite; Political elites; Postcommunism; Postkomunizem; Capitalism; Kapitalizem; Social state; Socialna država; welfare state; Social inequality; Družbena neenakost; Slovenia; Slovenija; Estonia; Estonian Soviet Socialist Republic; Estonija; politična elita